(untitled) (Marketing Journal, 2025)
The construction industry is becoming more integrated with modern technologies, leading to the emergence of smart services. This article analyzes the primary benefits of implementing these services in construction companies, with the most significant being a boost in project efficiency, cost optimization, and enhanced safety. Technologies like Digital Twin, Building Information Modeling (BIM), construction robots, and autonomous vehicles are revolutionizing project management. They enable the automation of construction processes and precise control of material usage. As a result, companies can use their resources more efficiently and become more competitive. Furthermore, smart services increase the transparency of construction processes and improve communication among all project participants. Data is centralized in one location through sensors, real -time monitoring systems, and cloud platforms. This accelerat es and improves the accuracy of decision -making, which is crucial for reducing unexpected risks, enhancing work quality, and ensuring strict adherence to safety protocols. Ultimately, smart services not only simplify the construction process but also move the entire industry toward a more innovative and sustainable future.